Incorporating Marketing Component in Strategic Research Extension Plan (SREP) of a District - M.A. Kareem,; B. K. Paty, (Journal of Agricultural Extension Management, 2014)
The Strategic Research and Extension Plan (SREP) is a vital document prepared at the Agricultural Technology Management Agency (ATMA) level for identifying research and extension gaps. In the first phase of the preparation of SREPs, the marketing component could not be incorporated due to different systemic reasons. Hence, MANAGE has taken up action research in Warangal district of Andhra Pradesh to incorporate the marketing component in the SREP of the District. Based on research experience and interaction with field functionaries, the fundamental steps for incorporation of marketing components in SREP have been arrived at. The components of the marketing aspects of Agriculture produce, from the vie¾point of preparation of SREP, can broadly be classified as infrastructure (hardware) and different marketing practices (software) such as direct marketing, group marketing, contract farming, processing and value addition, spot marketing, futures marketing, retail chain linkage, support price mechanism, export marketing etc. There is a need for a plan for each of these marketing components at the district level. The basic formats for development of SREP for marketing components have also been developed in consultation with the field officers. This paper focuses on these aspects with a hope that this would help ATMAs across the country. Considering that all the states have already started revisiting their SREPs, the results of this ongoing action research are expected to provide some timely inputs to incorporate the agricultural marketing components in terms of both hardware and software aspects